Evidence of an additional centre of apple domestication in Iran, with contributions from the Caucasian crab apple Malus orientalis Uglitzk. to the cultivated apple gene pool - Hamid Bina; Hamed Yousefzadeh; Anthony Venon; Carine Remoué; Agnès Rousselet; Matthieu Falque; Shadab Faramarzi; Xilong Chen; Jarkyn Samanchina; David Gill; Akylai Kabaeva; Tatiana Giraud; et al. (Molecular Ecology, 2022)
Divergence processes in crop‐wild fruit tree complexes in pivotal regions for plant domestication such as the Caucasus and Iran remain little studied. We investigated anthropogenic and natural divergence processes in apples in these regions using 26 microsatellite markers amplified in 550 wild and cultivated samples. We found two genetically distinct cultivated populations in Iran that are differentiated from Malus domestica , the standard cultivated apple worldwide. Coalescent‐based inferences showed that these two cultivated populations originated from specific domestication events of Malus orientalis in Iran. We found evidence of substantial wild‐crop and crop–crop gene flow in the Caucasus and Iran, as has been described in apple in Europe. In addition, we identified seven genetically differentiated populations of wild apple ( M. orientalis ), not introgressed by the cultivated apple. Niche modelling combined with genetic diversity estimates indicated that these wild populations likely resulted from range changes during past glaciations. This study identifies Iran as a key region in the domestication of apple and M. orientalis as an additional contributor to the cultivated apple gene pool. Domestication of the apple tree therefore involved multiple origins of domestication in different geographic locations and substantial crop‐wild hybridization, as found in other fruit trees. This study also highlights the impact of climate change on the natural divergence of a wild fruit tree and provides a starting point for apple conservation and breeding programmes in the Caucasus and Iran.

Deciphering the genetics of flowering time by an association study on candidate genes in bread wheat (Triticum aestivum L.) - Michel Rousset; Isabelle Bonnin; Carine Remoué; Matthieu Falque; Bénédicte Rhoné; Jean-Baptiste Veyrieras; Delphine Madur; Alain Murigneux; François Balfourier; Jacques Le Gouis; Sylvain Santoni; Isabelle Goldringer (Theoretical and Applied Genetics, 2011)

Molecular Evolution of the Opaque-2 Gene in Zea mays L. - Anne-Marie Henry; Domenica Manicacci; Matthieu Falque; Catherine Damerval (Journal of Molecular Evolution, 2005)